Protective film with low dynamic friction coefficient and high water drop angle and preparation method thereof

Through the collaborative design of low precipitation protective layer and low precipitation adhesive layer, combined with UV hardened adhesive and post-cured layer, the problem of reduced performance of hardened protective film in production, transportation and storage is solved, and the low friction coefficient of the hardened layer is achieved and High water drop angle characteristics improve scratch resistance, stain resistance and slippage.

CN119242201AInactive Publication Date: 2025-01-03DONG GUAN SUPER NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411504686.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-26
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The hardened protective film is easily contaminated with dirt and scratches during production, transportation and storage. The pressure-sensitive adhesive that protects the carrier volatiles small molecular substances under high temperature and long-term conditions, reducing the scratch resistance and dirt resistance of the hardened layer. and smoothness affect the performance.

Method used

Using low precipitation protective layer and low precipitation glue layer, through the coordinated combination of silicone, silicone resin and nano-silicon sol, combined with catalyst and crosslinking agent, a low dynamic friction coefficient high water droplet angle protective film is prepared, and the low precipitation glue layer is reduced to a smaller Molecular substances precipitate to maintain adhesion and stability. The hardened layer is cured by UV hardening glue, and the post-cured layer provides buffer protection.

Benefits of technology

Under long-term processing, transportation and storage conditions, the surface of the hardened layer maintains a low coefficient of friction and high water drop angle performance, improving wear resistance, stain resistance and slippage, solving the difficulty of traditional protective films to achieve low coefficient of friction and high simultaneously The problem of water drop angle, and the surface is smoother and smoother.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242201A_ABST
    Figure CN119242201A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electronic product protective films, and discloses a low-dynamic-friction-coefficient and high-water-drop-angle protective film and a preparation method thereof. The protective film with the low dynamic friction coefficient and the high water drop angle comprises a low-precipitation protective layer, a low-precipitation adhesive layer, a hardened layer, a post-curing layer and an adhesive layer which are sequentially attached from top to bottom, the low-precipitation glue layer is prepared by curing low-precipitation glue prepared from the following raw materials in parts by weight: 90-100 parts of organic silica gel, 140-190 parts of organic silicon resin, 2-4 parts of nano silica sol, 3-5 parts of a catalyst, 2-3 parts of a cross-linking agent and 300-400 parts of a solvent. Compared with the prior art, the low-precipitation adhesive layer has good low-precipitation performance and good protection stability on the hardened layer, the surface performance of the hardened layer of the prepared protective film is not affected, and the prepared protective film with the low dynamic friction coefficient and the high water drop angle has good scraping resistance, pollution resistance and smoothness in the application process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of protective films for electronic products, and more specifically, to a protective film with a low dynamic friction coefficient and a high water drop angle and a preparation method thereof. Background Art

[0002] With the development of electronic product technology and consumers' increasing requirements for electronic products, the styles and specifications of electronic products are becoming more diversified and thinner. The display screen of electronic products is an indispensable and important accessory in electronic products. Among them, the curved display screen is a display screen using flexible plastic, which can make the screen of electronic products thinner, lighter and lower in power consumption, and increase the viewing angle of the display screen, thereby improving the comfort of using electronic products.

[0003] In order to improve the protective performance of curved display screens, it is generally necessary to adhere a hardened protective film to the surface of the curved display screen. The hardened protective film is generally composed of an adhesive layer, a PET layer and a hardened layer, which can better improve the flexibility, scratch resistance and anti-fingerprint performance of the curved display screen.

[0004] During the production, processing, transportation and storage of the hardened protective film, the surface of the hardened layer is easily contaminated with dirt or scratched. Therefore, a protective carrier needs to be attached to the surface of the hardened layer of the hardened protective film, and the protective carrier plays a better protective role on the hardened layer; the protective carrier is generally a release film coated with a pressure-sensitive adhesive. Since the hardened protective film needs to go through preparation steps such as baking and drying during the entire processing process, and it will also undergo long-term transportation and storage afterwards, under long-term processing, transportation and storage conditions, the pressure-sensitive adhesive of the protective carrier will volatilize some small molecular substances, such as silicone oil or plasticizers, etc. These components evaporate to the surface of the hardened layer, which can easily reduce the scratch resistance, anti-fouling performance and smoothness of the surface of the hardened layer, thereby affecting the performance of the hardened protective film. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a low dynamic friction coefficient and high water drop angle protection film and a preparation method thereof.

[0006] In the first aspect, the present application provides a low dynamic friction coefficient and high water drop angle protective film, which adopts the following technical scheme: a low dynamic friction coefficient and high water drop angle protective film, comprising a low precipitation protective layer, a low precipitation adhesive layer, a hardening layer, a post-curing layer and an adhesive layer which are sequentially laminated from top to bottom, wherein the low precipitation adhesive layer is made of a low precipitation adhesive made of the following raw materials in parts by weight and cured:

[0007] By adopting the above technical solution, the low precipitation protective layer plays the role of supporting the low precipitation adhesive layer, and at the same time can play the role of blocking pollutants in the external environment, reduce the contamination of the hardened layer, and ensure the cleanliness of the hardened layer. The low precipitation adhesive layer is made of low precipitation adhesive made of organic silica gel, organic silicone resin, nano silica sol, catalyst, cross-linking agent and solvent, and cross-linked under the action of catalyst and cross-linking agent through the synergistic compounding of organic silica gel, organic silicone resin and nano silica sol. The microporous structure of nano silica sol has good adsorption capacity and permeability, which can further improve the cross-linking density of the silica gel system. The low precipitation adhesive layer can not only significantly reduce the precipitation of small molecules, but also maintain good adhesion and stability, avoiding the small molecules released under high temperature and long-term storage conditions in the subsequent process to contaminate the surface of the hardened layer, thereby ensuring that the surface of the hardened layer has excellent low friction coefficient and high water drop angle characteristics, with low precipitation protective layer and low precipitation adhesive layer as protection carriers. The hardened layer is obtained by curing UV hardening adhesive, giving the protective film a good surface hardness, good wear resistance, anti-fouling and smoothness. The post-curing layer can provide a good buffering and protective effect on the hardened layer, and can further enhance the strength and stability of the protective film.

[0008] When in use, just tear off the low precipitation protective layer together with the low precipitation adhesive layer. The protective film prepared in this way still maintains the performance of low friction coefficient and high water drop angle on the surface of the hardened layer under long-term processing, transportation and storage conditions, and has good wear resistance, anti-fouling and smoothness; it solves the problem that traditional hardened films cannot achieve low friction coefficient and high water drop angle at the same time. Compared with some protective films on the market that are made with microporous structures or uneven surfaces to improve anti-fouling effects, the protective film of this application has better surface flatness and smoothness.

[0009] Preferably, the organic silica gel is composed of a first raw rubber, a second raw rubber and a third raw rubber in a weight ratio of 1:(1-2):(2-3), the first silica gel is methyl silicone rubber raw rubber, and the molecular weight of the first silica gel is 600,000-700,000; the second silica gel is methyl silicone rubber raw rubber, and the molecular weight of the second silicone rubber is 400,000-500,000; the third silica gel is methyl vinyl silicone rubber raw rubber, the molecular weight of the third silica gel is 50,000-100,000, and the vinyl molar content is 0.5-1%.

[0010] By adopting the above technical scheme, the organic silica gel is composed of three raw rubbers with different molecular weights, wherein the first raw rubber and the second raw rubber are both methyl silicone rubber raw rubber, and are compounded with preferably dosage and molecular weight, the molecular segments of methyl silicone rubber raw rubbers with different molecular weights can be interwoven and filled with each other, thereby improving the structural stability and structural density of the low precipitation rubber layer; the third raw rubber has a lower molecular weight, so that the prepared low precipitation rubber can improve the viscosity of the low precipitation rubber and has good fluidity, and the molecular segment contains vinyl functional groups, which can be cross-linked and filled in the dispersed structure interwoven by the first raw rubber and the second raw rubber, thereby improving the cohesion of the molecular segments in the prepared low precipitation rubber layer, forming a more dense interwoven and cross-linked network structure, thereby reducing the precipitation performance of the low precipitation rubber layer, so that the hardened layer of the protective film can maintain a low friction coefficient and a high water drop angle, and improve the scratch resistance, stain resistance and smoothness of the protective film.

[0011] Preferably, the organic silicone resin is one or a combination of methyl silicone resin, methyl phenyl silicone resin and methyl MQ silicone resin.

[0012] By adopting the above technical scheme, the above silicone resin has good wear resistance and mechanical properties, can be better compatible with organic silicone and other components, form a low precipitation adhesive layer with a stable silicone structure, further reduce the precipitation performance of the low precipitation layer, and improve the cohesion and performance stability of the low precipitation layer.

[0013] Preferably, the catalyst is one or a combination of an organic tin catalyst, an organic bismuth catalyst, an organic amine catalyst and a titanate catalyst.

[0014] By adopting the above technical scheme, the above cross-linking agent can greatly improve the reaction stability of organic silica gel, organic silicone resin, nano silica sol and cross-linking agent, further reduce the precipitation of small molecular substances, so that the prepared protective film still maintains the characteristics of low friction coefficient and high water drop angle under long-term processing, transportation and storage conditions.

[0015] Preferably, the cross-linking agent is one or a combination of triethanolamine, glycerol, mesityl alcohol, triisopropanolamine and trimethylolethane.

[0016] By adopting the above technical solution, the above cross-linking agent can improve the cross-linking performance of organic silica gel, organic silicone resin and nano silica sol, improve the cross-linking density of the low precipitation adhesive layer, and form a low precipitation adhesive layer with good flexibility and low precipitation performance.

[0017] Preferably, the solvent is toluene and / or xylene.

[0018] By adopting the above technical solution, the above solvent can form a stable dispersion system, so that each component is cross-linked and dispersed in the solvent, thereby improving the performance stability of the obtained low precipitation adhesive layer.

[0019] Preferably, the hardening layer is a UV hardening adhesive layer, and the UV hardening adhesive layer is obtained by curing UV hardening adhesive made of the following raw materials in parts by weight: Polyurethane acrylate 50-70 parts Methyl methacrylate 10-15 parts Pentaerythritol triacrylate 8-12 parts Dicyclopentenyl acrylate 6-10 parts 4-6 parts of triisopropylsilyl methacrylate 4-6 parts of tetraethylene glycol diacrylate 3-5 parts of cyclohexane-1,2-dicarboxylic acid diglycidyl ester Photoinitiator 5-8 parts 2-4 parts of catalyst.

[0020] By adopting the above technical scheme, polyurethane acrylate is used as the acrylate system of UV curing glue, which can effectively improve the hardness and wear resistance of the hardened layer, further improve the scratch resistance and surface smoothness of the hardened layer, reduce the friction coefficient, and improve the water drop angle on the surface of the hardened layer. Methyl methacrylate, pentaerythritol triacrylate, dicyclopentenyl acrylate, triisopropylsilyl methacrylate, tetraethylene glycol diacrylate and cyclohexane-1,2-dicarboxylic acid diglycidyl ester are used as functional monomers in an optimal amount, and a cross-linking reaction is carried out under the action of an initiator and a catalyst, wherein dicyclopentenyl acrylate and triisopropylsilyl methacrylate are used as end-capping agents for end-capping, thereby giving the hardened layer moderate hardness and flexibility. The hardened layer obtained has good cross-linking density and structural density, is not easy to react with the low precipitation glue layer during processing, and can maintain a high water drop angle and a low friction coefficient.

[0021] Preferably, the post-curing layer is a UV-curing acrylic adhesive.

[0022] By adopting the above technical solution, the UV-curing acrylic adhesive can form a stable bonding layer on the surface of the hardened layer, which has a good buffering and protective effect on the hardened layer, making the hardened layer not easily damaged.

[0023] In a second aspect, the present application provides a method for preparing a low dynamic friction coefficient and high water drop angle protection film, using the following technical solution: A method for preparing a low dynamic friction coefficient and high water drop angle protection film comprises the following steps: S1, coating the low precipitation adhesive on the surface of the low precipitation protective layer, and performing thermal curing to obtain a low precipitation adhesive layer; S2, coating a UV curing adhesive on the surface of the low precipitation adhesive layer, and UV curing it to obtain a hardened layer; S3, coating a UV curing acrylic adhesive on the surface of the hardened layer, and UV curing it to obtain a post-curing layer; S4, coating adhesive on the surface of the post-curing layer, performing heat curing, and rolling up to obtain a low dynamic friction coefficient and high water droplet corner protection film.

[0024] By adopting the above technical scheme, firstly, the low precipitation glue is coated on the surface of the low precipitation protective layer, and the low precipitation glue layer is obtained by thermal curing, and then the UV curing glue and UV curing acrylic adhesive are coated and cured in sequence to form a hardened layer and a post-cured layer, and finally the adhesive is coated on the surface of the post-cured layer and thermally cured and rolled up, so that the prepared protective film has good production, transportation and storage stability; by the process of coating the UV curing glue on the low precipitation glue layer, the hardened layer is uniformly cured on the surface of the low precipitation layer, the surface flatness and adhesion uniformity of the hardened layer are improved, and when used later, the low precipitation protective layer and the low precipitation glue layer are torn off without damaging the hardened layer.

[0025] Preferably, the curing temperature of step S1 is divided into two stages, the curing temperature of the first stage is 70-80°C, and the curing temperature of the second stage is 120-160°C.

[0026] By adopting the above technical scheme, better curing conditions can improve the uniformity and stability of the low precipitation adhesive layer during the curing process, avoiding local overheating or uneven heating that may occur during curing at a single temperature, which may cause uneven or uneven curing of the low precipitation adhesive layer, indicating the performance stability of the low precipitation adhesive layer, thereby improving the protective performance of the hardened layer.

[0027] In summary, this application has the following beneficial effects: 1. The low dynamic friction coefficient and high water drop angle protective film of the present application includes a low precipitation protective layer, a low precipitation adhesive layer, a hardening layer, a post-curing layer and an adhesive layer which are sequentially laminated from top to bottom. The low precipitation protective layer and the low precipitation adhesive layer serve as protective carriers of the hardening layer. The low precipitation adhesive layer is prepared by synergistic compounding of organic silica gel, organic silicone resin and nano-silica sol, and cross-linking under the action of a catalyst and a cross-linking agent. The low precipitation adhesive layer can not only significantly reduce the precipitation of small molecules, but also maintain good adhesion and stability, and avoid small molecules released under high temperature and long-term storage conditions in subsequent processes from contaminating the surface of the hardening layer, thereby ensuring that the surface of the hardening layer has excellent low friction coefficient and high water drop angle performance.

[0028] 2. By controlling the organic silicone to be composed of the first silicone, the second silicone and the third silicone, and the first silicone is a methyl silicone rubber raw rubber with a molecular weight of 600,000-700,000, the second silicone is a methyl silicone rubber raw rubber with a molecular weight of 400,000-500,000, and the third silicone is a vinyl silicone rubber raw rubber with a molecular weight of 50,000-100,000. Through the synergistic effect of the three, the cohesion of the molecular chain segments in the low precipitation adhesive layer is improved to form a more dense interweaving and cross-linking network structure, thereby reducing the precipitation performance of the low precipitation adhesive layer, so that the hardened layer of the protective film can maintain a low friction coefficient and a high water drop angle, thereby improving the scratch resistance, stain resistance and smoothness of the protective film.

[0029] 3. By using polyurethane acrylate as the main acrylic acid, and using preferably used amounts of methyl methacrylate, pentaerythritol triacrylate, dicyclopentenyl acrylate, triisopropylsilyl methacrylate, tetraethylene glycol diacrylate and cyclohexane-1,2-dicarboxylic acid diglycidyl ester as functional monomers, a cross-linking reaction is carried out under the action of an initiator and a catalyst to give the hardened layer moderate hardness and flexibility. The obtained hardened layer has good cross-linking density and structural density, is not easy to react with the low precipitation adhesive layer during processing, and can maintain a high water drop angle and a low friction coefficient.

[0030] 4. The preparation process of the present application is to first apply low precipitation glue on the surface of the low precipitation protective layer, and then apply UV curing glue on the low precipitation glue layer, so that the hardened layer is evenly cured on the surface of the low precipitation layer, thereby improving the surface flatness and adhesion uniformity of the hardened layer. Finally, the post-curing layer and the adhesive layer are cured on the surface of the hardened layer. The obtained protective film has good production, transportation and storage stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the interlayer structure of a low dynamic friction coefficient and high water drop angle protection film of the present application.

[0032] Figure numerals: 1, low precipitation protective layer; 2, low precipitation adhesive layer; 3, hardening layer; 4, post-curing layer; 5, adhesive layer. DETAILED DESCRIPTION

[0033] The following is combined with Figure 1 The present application is further described in detail with reference to the accompanying drawings and embodiments.

[0034] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Nano silica sol: CY-YJ01; 2. Polyurethane acrylate: Allnex EBECRYL 8110; 3. Pentaerythritol triacrylate: Lankelu L-61030PETA; 4. Dicyclopentenyl acrylate: CAS No. 12542-30-2, content 99%; 5. Triisopropylsilyl methacrylate: CAS No. 134652-60-1, content 99%; 6. Tetraethylene glycol diacrylate: CAS No. 17831-71-9, content 90%; 7. Cyclohexane-1,2-dicarboxylic acid diglycidyl ester: content 98%, CAS number 5493-45-8; 8. Methyl silicone resin: Shengbang silicone SI-MQ102; 9. Methylphenyl silicone resin: Sihai 9602.

[0035] Preparation example of low precipitation glue Preparation Example 1 Preparation Example 1 discloses a low precipitation gel, which is prepared by the following steps: 14 kg of methyl silicone resin as an organic silicone resin and 30 kg of xylene as a solvent are added to a reactor, the temperature is raised to 60°C and stirred to dissolve, then 9 kg of organic silica gel (composed of 6 kg of methyl silicone rubber raw rubber and 3 kg of methyl vinyl silicone rubber raw rubber, the molecular weight of the methyl silicone rubber raw rubber is 600,000-700,000, the molecular weight of the methyl vinyl silicone rubber raw rubber is 50,000-100,000, and the vinyl molar content is 0.5-1%), 0.2 kg of nano silica sol, 0.2 kg of a cross-linking agent (composed of 0.1 kg of triethanolamine and 0.1 kg of trimethylolpropane) and 0.3 kg of an organic tin catalyst (dibutyltin dilaurate) are added, and the reaction is carried out for 2.5 hours to obtain a low precipitation glue.

[0036] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0037] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the organic silica gel is different. The organic silica gel in Preparation Example 4 is composed of a first raw rubber, a second raw rubber and a third raw rubber. The first raw rubber is methyl silicone rubber raw rubber with a molecular weight of 600,000-700,000 and an amount of 4 kg; the second raw rubber is methyl silicone rubber raw rubber with a molecular weight of 400,000-500,000 and an amount of 2 kg; the third raw rubber is methyl vinyl silicone rubber raw rubber with a molecular weight of 50,000-100,000 and a vinyl molar content of 0.5-1%, and an amount of 3 kg. The rest is the same as Preparation Example 1.

[0038] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 4 is that the amounts of the first raw rubber, the second raw rubber and the third raw rubber are different. The amount of the first raw rubber is 1.5 kg, the amount of the second raw rubber is 3 kg, and the amount of the third raw rubber is 4.5 kg. The rest is the same as Preparation Example 4.

[0039] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the amounts of the first raw rubber, the second raw rubber and the third raw rubber are different. The amount of the first raw rubber is 2.25 kg, the amount of the second raw rubber is 2.25 kg, and the amount of the third raw rubber is 4.5 kg. The rest is the same as Preparation Example 4.

[0040] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the molecular weight of the third raw rubber is 500,000-600,000, the vinyl molar content is 0.5-1%, and the rest is the same as Preparation Example 5.

[0041] Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of nano-silica sol is replaced by silicon dioxide with a particle size of 50 nm, and the rest is the same as Preparation Example 1.

[0042] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of the organic silicone resin is replaced with organic silica gel, and the rest is the same as Preparation Example 1.

[0043] Preparation example of UV curable adhesive Preparation Example 8 Preparation Example 8 discloses a UV curable adhesive, which is prepared by the following steps: 5kg of polyurethane acrylate, 1kg of methyl methacrylate, 0.8kg of pentaerythritol triacrylate, 0.6kg of tetraethylene glycol diacrylate, 0.5kg of cyclohexane-1,2-dicarboxylic acid diglycidyl ester and 0.2kg of dibenzoyl peroxide were added into the reactor as catalyst, the temperature was raised to 70°C, the reaction was carried out for 1h, 0.6kg of dicyclopentenyl acrylate and 0.5kg of triisopropylsilyl methacrylate were added, the reaction was continued for 60min, and 0.8kg of photoinitiator (composed of 0.4kg of 2-hydroxy-2-methylpropiophenone and 0.4kg of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester) was added, and the mixture was stirred evenly to obtain UV curing glue.

[0044] Preparation Examples 9-10 The difference between Preparation Examples 9-10 and Preparation Example 8 is that the amounts of raw materials used and the preparation conditions are different, see Table 2 below for details.

[0045] Table 2 Raw material dosage and preparation conditions of Preparation Examples 8-10 Preparation Comparative Example 3 The difference between Preparation Comparative Example 3 and Preparation Example 8 is that an equal amount of cyclohexane-1,2-dicarboxylic acid diglycidyl ester is replaced by glycidyl methacrylate, and the rest is the same as Preparation Example 8.

[0046] Preparation Comparative Example 4 The difference between Preparation Comparative Example 4 and Preparation Example 8 is that an equal amount of tetraethylene glycol diacrylate is replaced by pentaerythritol triacrylate, and the rest is the same as Preparation Example 8.

[0047] Preparation Comparative Example 5 The difference between Preparation Comparative Example 5 and Preparation Example 8 is that an equal amount of triisopropylsilyl methacrylate is replaced by dicyclopentenyl acrylate, and the rest is the same as Preparation Example 8.

[0048] Preparation Comparative Example 6 The difference between Preparation Comparative Example 6 and Preparation Example 8 is that an equal amount of dicyclopentenyl acrylate is replaced by hydroxyethyl methacrylate, and the rest is the same as Preparation Example 8. Example

[0049] Example 1 Example 1 discloses a low dynamic friction coefficient and high water drop angle protection film, referring to Figure 1 , including a low precipitation protective layer 1, a low precipitation adhesive layer 2, a hardening layer 3, a post-curing layer 4 and an adhesive layer 5 which are sequentially laminated from top to bottom.

[0050] The low dynamic friction coefficient and high water drop angle protective film is prepared by the following steps: S1. The low precipitation glue prepared in Preparation Example 1 is coated on the surface of the low precipitation protective layer, first cured at a temperature of 70° C. for 5 min, and then cured at a temperature of 160° C. for 3 min to obtain a low precipitation glue layer. The low precipitation protective layer is a low precipitation PET film purchased from Shengtai, model ST-D04, and the thickness of the low precipitation glue layer is 20 μm; S2. Apply UV curing glue on the surface of the low precipitation glue layer. The UV curing glue was purchased from Gaotu, model GT3311, and the curing energy was 100mW / cm 2 , curing for 10 seconds under ultraviolet light with a wavelength of 240-365nm to obtain a hardened layer with a thickness of 2μm; S3, apply UV curing acrylic adhesive on the surface of the hardened layer. The UV curing acrylic adhesive was purchased from EPO-TEK OG675 and the curing energy was 100mW / cm 2 , curing for 35 seconds under ultraviolet light with a wavelength of 240-365 nm to obtain a post-cured layer, the thickness of the post-cured layer being 50 μm; S4. Apply adhesive on the surface of the post-curing layer. The adhesive is derived from heat-curing silicone optical adhesive MY 5123AB. Curing is performed at a temperature of 70°C for 5 minutes to form an adhesive layer. The thickness of the adhesive layer is 20 μm. The layer is rolled up to obtain a low dynamic friction coefficient and high water droplet corner protection film.

[0051] Embodiment 2-4 The difference between Example 2-4 and Example 1 is that the preparation process parameters are different, see Table 3 below for details.

[0052] Table 3 Preparation process parameters of Examples 1-4 Embodiment 5-8 The difference between Examples 5-8 and Example 2 is that the hardened layers are different, see Table 4 below for details.

[0053] Table 4 Sources of the hardened layers of Examples 5-8 Example Source of hardened layer Example 5 Preparation Comparative Example 3 Example 6 Preparation Comparative Example 4 Example 7 Preparation Comparative Example 5 Example 8 Preparation Comparative Example 6 Examples 9-12 The difference between Examples 9-12 and Example 2 is that the low precipitation adhesive layer is different, see Table 5 below for details.

[0054] Table 5 Sources of low precipitation adhesive layer of Examples 9-12 Example Source of low precipitation layer Example 9 Preparation Example 4 Example 10 Preparation Example 5 Embodiment 11 Preparation Example 6 Example 12 Preparation Example 7 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the low precipitation adhesive layer in Comparative Example 1 is derived from the preparation of Comparative Example 1, and the rest is the same as Example 2.

[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that the low precipitation adhesive layer in Comparative Example 2 is derived from the preparation of Comparative Example 2, and the rest is the same as Example 2.

[0056] Performance testing The following tests were conducted on the low dynamic friction coefficient and high water droplet angle protective films prepared in Examples 1-12 and Comparative Examples 1-2. During the tests, the low precipitation protective layer and the low precipitation adhesive layer were torn apart, and the performance of the hardened layer surface was tested: 1. Dynamic friction coefficient test: Refer to the test method in GB / T 22895-2008, use a dynamic friction coefficient tester, the slider weight is 200g, the slider movement speed is 150mm / min, test the dynamic friction coefficient of the hardened surface of the protective film, record it as the dynamic friction coefficient before wiping; then use a dust-free cloth dipped in anhydrous ethanol, wipe the hardened surface back and forth three times, and continue to test the dynamic friction coefficient of the hardened surface after wiping after the anhydrous ethanol evaporates, record it as the dynamic friction coefficient after wiping, test and record the test results. The smaller the dynamic friction coefficient, the better the surface smoothness; 2. Water drop angle test: Use a water drop angle tester to place the protective film to be tested on the test platform and test the water drop angle, which is recorded as the water drop angle before wiping; then use a dust-free cloth dipped in anhydrous ethanol to wipe the protective film back and forth three times, and continue to test the water drop angle of the protective film after the anhydrous ethanol evaporates, which is recorded as the water drop angle after wiping. Test and record the test results. The larger the water drop angle, the better the anti-fouling effect; 3. Wear resistance test: Use a wear tester and steel wool (steel wool model: Bangshida #0000) to apply a load of 1kg to a 2*2cm indenter at a speed of 60 times / minute with a controlled stroke of 20mm. Rub back and forth on the hardened layer surface of the protective film. When wear marks appear on the hardened layer surface, stop the test and record the number of frictions. The following are the performance test data of the low dynamic friction coefficient and high water droplet angle protection films prepared in Examples 1-12 and Comparative Examples 1-2, see Table 6 below for details.

[0057] Table 6 Performance test data of Examples 1-12 and Comparative Examples 1-2 Combining Examples 1-8 and Table 6, it can be concluded that the hardened layer prepared by polyurethane acrylate, methyl methacrylate, pentaerythritol triacrylate, dicyclopentenyl acrylate, triisopropylsilyl methacrylate, tetraethylene glycol diacrylate, cyclohexane-1,2-dicarboxylic acid diglycidyl ester, initiator and catalyst of the present application has good wear resistance, anti-fouling and smoothness; compared with Example 1, the water drop angle of the hardened layer prepared in Example 2 is increased by 4°, the change rate of the water drop angle after wiping with anhydrous ethanol is also small, the dynamic friction coefficient is increased by 0.21, and the number of wear resistance is increased by 460 times; Compared with Example 1, Examples 5-8 have a lower water drop angle, an increased friction coefficient, and a reduced wear times. It can be seen that the polyurethane acrylate, methyl methacrylate, pentaerythritol triacrylate, dicyclopentenyl acrylate, triisopropylsilyl methacrylate, tetraethylene glycol diacrylate, and cyclohexane-1,2-dicarboxylic acid diglycidyl ester of the present application have a good synergistic effect. The obtained hardened layer has good cross-linking density, wear resistance and anti-fouling properties, is not easy to react with the low precipitation adhesive layer during processing and storage, can maintain a high water drop angle and a low friction coefficient, and has stable performance.

[0058] Further, in combination with Example 2 and Examples 9-12, Comparative Examples 1-2 and Table 6, it can be concluded that the use of the low precipitation adhesive layer of the present application in combination with the hardening layer of the present application can improve the protective performance of the hardening layer and reduce the problem of reduced surface anti-fouling and smoothness of the hardening layer due to processing, storage and other conditions. Compared with Example 2, Comparative Example 1 replaces the nano-silica sol with silicon dioxide in equal amounts. Although the water drop angle of the hardened layer of the protective film obtained is slightly reduced, the dynamic friction coefficient is significantly increased by 0.6. This may be because the addition of silicon dioxide forms a microscopic uneven surface on the surface of the low precipitation adhesive layer, which affects the flatness of the surface of the hardened layer during processing and storage, thereby significantly increasing the dynamic friction coefficient and reducing the wear resistance; Compared with Example 2, Comparative Example 2 replaces the silicone resin with organic silica gel. The water drop angle of the surface of the hardened layer obtained is significantly reduced by 8°, and the dynamic friction coefficient is increased by 0.25 , the wear resistance is also significantly reduced, which may be because the synergistic effect of the silicone resin and the silicone gel is reduced, thereby reducing the cross-linking density of the low precipitation layer, reducing the cohesive force in the low precipitation layer, and further affecting the wear resistance, smoothness and anti-fouling properties of the hardened layer; and Example 10, compared with Example 2, further optimizes the composition of the silicone gel, can further improve the cross-linking stability of the low precipitation layer, reduce the problem of volatile substances affecting the hardened layer during processing or storage, the water drop angle of the hardened layer can reach 122°, the dynamic friction coefficient reaches 0.02, and the wear resistance times reaches 2500 times.

[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low dynamic friction coefficient and high water drop angle protection film, characterized in that: The invention comprises a low precipitation protective layer, a low precipitation adhesive layer, a hardening layer, a post-curing layer and an adhesive layer which are sequentially laminated from top to bottom, wherein the low precipitation adhesive layer is made by curing a low precipitation adhesive obtained from the following raw materials in parts by weight: 90-100 parts of organic silica gel 140-190 parts of silicone resin 2-4 parts of nano silica sol 3-5 parts of catalyst 2-3 parts of crosslinking agent 300-400 parts of solvent.

2. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The organic silica gel is composed of a first raw rubber, a second raw rubber and a third raw rubber in a weight ratio of 1: (1-2): (2-3), wherein the first silica gel is methyl silicone rubber raw rubber, and the molecular weight of the first silica gel is 600,000-700,000; the second silica gel is methyl silicone rubber raw rubber, and the molecular weight of the second silica gel is 400,000-500,000; the third silica gel is methyl vinyl silicone rubber raw rubber, and the molecular weight of the third silica gel is 50,000-100,000, and the vinyl molar content is 0.5-1%.

3. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The organic silicone resin is one or a combination of methyl silicone resin, methyl phenyl silicone resin and methyl MQ silicone resin.

4. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The catalyst is one or a combination of an organic tin catalyst, an organic bismuth catalyst, an organic amine catalyst and a titanate catalyst.

5. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The cross-linking agent is one or a combination of triethanolamine, glycerol, mesityl alcohol, triisopropanolamine and trimethylolethane.

6. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The solvent is toluene and / or xylene.

7. A low dynamic friction coefficient and high water drop angle protection film according to any one of claims 1 to 6, characterized in that: The hardened layer is a UV hardened adhesive layer, and the UV hardened adhesive layer is obtained by curing UV hardened adhesive made of the following raw materials in parts by weight: Polyurethane acrylate 50-70 parts Methyl methacrylate 10-15 parts Pentaerythritol triacrylate 8-12 parts Dicyclopentenyl acrylate 6-10 parts 4-6 parts of triisopropylsilyl methacrylate 4-6 parts of tetraethylene glycol diacrylate 3-5 parts of cyclohexane-1,2-dicarboxylic acid diglycidyl ester Photoinitiator 5-8 parts 2-4 parts of catalyst.

8. The low dynamic friction coefficient and high water drop angle protection film according to claim 1, characterized in that: The post-curing layer is a UV-curing acrylic adhesive.

9. A method for preparing a low dynamic friction coefficient and high water drop angle protection film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, coating the low precipitation adhesive on the surface of the low precipitation protective layer, and performing thermal curing to obtain a low precipitation adhesive layer; S2, coating the surface of the low precipitation adhesive layer with UV curing adhesive, and performing UV curing to obtain a hardened layer; S3, coating a UV-curable acrylic adhesive on the surface of the hardened layer and performing UV curing to obtain a post-cured layer; S4, coating adhesive on the surface of the post-curing layer, performing heat curing, and rolling up to obtain a low dynamic friction coefficient and high water droplet corner protection film.

10. The method for preparing a low dynamic friction coefficient and high water droplet angle protection film according to claim 9, characterized in that: The curing temperature of step S1 is divided into two stages, the curing temperature of the first stage is 70-80°C, and the curing temperature of the second stage is 120-160°C.

Citation Information

Patent Citations

  • Organic silicon pressure sensitive adhesive and pressure sensitive adhesive tape or film

    CN106753195A

  • TPU silica gel protective film for 3D curved surface mobile phone and preparation method thereof

    CN110484156A

  • UV photocuring 3D protective film and preparation method thereof

    CN112175539A

  • Gluing agent for mica plate as well as preparation method and application of sizing agent

    CN114479756A

  • Silica gel glue, preparation method of silica gel glue, silica gel protective film and preparation method of silica gel protective film

    CN115806798A